KOLERASI ASUPAN ZAT GIZI MAKRO PADA MENU MAKAN HARIAN TERHADAP STATUS GIZI REMAJA DI ASRAMA PUTRI STIKES MUHAMMADIYAH CIREBON - Hidayah, Fika Nurul; Triwahyuningsih, Ria Yulianti; Kumalasary, Diyanah; Iskandar, Syifa Fauziah (JURNAL KESEHATAN INDRA HUSADA, 2024)
Food needs planning is an activity to calculate the food needs needed for food procurement in institutions by paying attention to the feeding regulations in each institution, served in an attractive and fun way for students (and school officials) which aims to improve and maintain the nutritional status of school children, increase attendance at school (not often sick), improve academic achievement and stimulate and support Nutrition Education in the Curriculum. Purpose: to determine the application of daily menu to macro nutritional intake, and nutritional status in STIKes Muhammadiyah Cirebon dormitory. This study used a type of quantitative research with a cross sectional approach and the Kruskal Wallis test. The results showed that 81% of adolescents had an energy deficit, 41% had a protein deficit, 42% had a normal fat intake, and 37% had a normal carbohydrate intake. There was no relationship between energy intake and nutritional status (P=0.416), protein intake and nutritional status was not related (P=0.610), fat intake was related to nutritional status (P=0.040) and carbohydrate intake was related to nutritional status (P=0.000). The results of the ordinal logistic regression analysis test found that all independent variables had a p-value > 0.05 so that it could be interpreted that there were no independent variables that affected nutritional status.